FORMATION AND DEVELOPMENT OF FINTECH IN UKRAINE - Tetiana Mulyk (Izdevnieciba "Baltija Publishing", 2022)
The purpose of the paper is to analyze the theoretical situation and current state of the domestic FinTech market, as well as conducting a SWOT analysis of the domestic FinTech market and determining its strengths and weaknesses, opportunities and threats. Methodology. The theoretical and methodological basis of the study are modern theories of market economy. During the study the following methods were used: inductive, deductive, analysis and synthesis, historical and logical, graphic. Results. Scientific approaches to understanding the essence of the term FinTech were assessed. The multifaceted and versatile content of the term "FinTech" caused various differences and peculiarities in the definition of this category in scientific sources. Scientists interpret FinTech as innovative technologies and business models, as technologies, industries, services, etc. However, each of the presented definitions traces their main feature, which is that FinTech really cannot work without digital technology. The origin of the term FinTech, which is a relatively new industry not only in Ukraine but also all over the world, was investigated. It has been established that the term emerged in the economic literature in the early 1990s, when the Internet began to develop. The growing popularity of FinTech began in 2008, when the global financial crisis and its consequences forced financial companies to cut costs. It is established that the development of financial technology in Ukraine is especially noticeable in the last five years. The article analyzes: the complex of factors that led to the rapid development of FinTech, the sources of FinTech companies' financing in Ukraine, the distribution of FinTech companies by field of activity in Ukraine and the number of employees, the markets in which Ukrainian FinTech companies operate, the main reasons that hinder its development in Ukraine. Practical implications. As a result of the research, a SWOT-analysis of the domestic FinTech market was carried out and its strengths, weaknesses, opportunities and threats that can be used by various FinTech industry actors to develop the FinTech market in Ukraine and improve FinTech products were identified.